Unsur psikologi Maslow dalam novel terpilih - Hashim Nurhamizah, Mat Hussain Eizah, Mohd Nasir Nur Yuhanis, (Universiti Pendidikan Sultan Idris, 2017)
Unsur psikologi Maslow dalam novel terpilih by Hashim Nurhamizah, Mat Hussain Eizah, Mohd Nasir Nur Yuhanis,